Exploring Pre-Service Teacher's Professional Identity Using Metaphors: Implication For Education Curricula (Linguistic, English Education and Art (LEEA) Journal, 2023)
Although professional identity formation is a key idea in education, little is known about the procedure from the viewpoint of the students. The goal of this study is to evaluate the limitations of the metaphors used by Indonesian first-graders studying education to characterize teachers in the context of developing a professional identity. Both qualitative and quantitative analyses of the data were done. Four conceptual themes were comprised of a total of 39 well-articulated metaphorical pictures. Despite some restrictions, the use of metaphors to create and explain professional identities can be useful in reflecting the values and beliefs of matriculating to education school, as well as in providing some insight into the personal beliefs and values of matriculating assistance with and suggestions for curriculum conception. Keywords: Education Curriculum; Education Students; Metaphors; Professional Identity